Participatory Engagement And Women’s Empowerment In An Alternative Public Health Model: A Case Study Of Buddhist Medicine Foundation Of Thailand - Krutmechai, Montawadee (2017)
It aims at identifying the nature of participatory engagement in BMFT, and the strategies used in creating participatory culture in the organisation. The study also explores whether BMFT’s activities empower women, and assesses whether BMFT has the characteristics and potentials of a social movement. A mixed mode approach comprising survey questionnaires, in-depth interviews and participatory observations was employed to obtain data from seven groups of respondents, representing five regions of Thailand. A total of 1,413 respondents filled up the survey questionnaires and 60 respondents participated in the in-depth interviews.